2017
DOI: 10.1101/132514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population temporal structure supplements the rate code during sensorimotor transformations

Abstract: Sensory-to-motor transformations are critically mediated by neurons in premotor brain networks whose evolving activities represent sensory, cognitive, and movement-related information. However, this multiplexing poses a conundrum: how does a decoder know precisely when to initiate a movement if such neurons are also active at times other than when a movement occurs? Extant models of movement generation that rely on firing rate, including rise-to-threshold, inhibitory gating, and dynamical switches at the popul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 72 publications
(131 reference statements)
3
12
0
Order By: Relevance
“…The only difference in this case was that the overall behavioral impact on the movement amplitudes ( D ) was smaller than with the near visual bursts (consistent with Figure 3—figure supplement 1 ). Note that this could reflect a lower likelihood of proper temporal alignment of far peripheral visual spikes with the population motor bursts for microsaccades, according to the novel hypothesis of Jagadisan and Gandhi, 2019 . Indeed, in Figure 6 and Figure 6—figure supplement 2 , we found that with proper temporal alignment, the impacts of individual movement-unrelated spiking on microsaccade amplitudes were quantitatively similar for both near and far neurons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only difference in this case was that the overall behavioral impact on the movement amplitudes ( D ) was smaller than with the near visual bursts (consistent with Figure 3—figure supplement 1 ). Note that this could reflect a lower likelihood of proper temporal alignment of far peripheral visual spikes with the population motor bursts for microsaccades, according to the novel hypothesis of Jagadisan and Gandhi, 2019 . Indeed, in Figure 6 and Figure 6—figure supplement 2 , we found that with proper temporal alignment, the impacts of individual movement-unrelated spiking on microsaccade amplitudes were quantitatively similar for both near and far neurons.…”
Section: Resultsmentioning
confidence: 99%
“…This is achieved through multiplexing of functions, either at the level of individual brain areas or even at the level of individual neurons themselves. For example, in different motor modalities like arm ( Alexander and Crutcher, 1990 ; Shen and Alexander, 1997 ; Breveglieri et al, 2016 ) or eye ( Goldberg and Wurtz, 1972b ; Goldberg and Wurtz, 1972a ; Wurtz and Goldberg, 1972 ; Mohler and Wurtz, 1976 ; Bruce and Goldberg, 1985 ; Jagadisan and Gandhi, 2019 ) movements, a large fraction of the neurons contributing to the motor command are also intrinsically sensory in nature, hence being described as sensory-motor neurons. In this study, we aimed to investigate the implications of such sensory and motor multiplexing using vision and the oculomotor system as our model of choice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to reconcile these seemingly discrepant results, particularly with respect to the latter set of studies, is that the transformation may occur in dorsal, visually-dominant layers and that the population activity doesn’t transition to the motoric layers until after the animal receives permission to produce a movement. This notion suggests that the gaze-centered signal, although thought to be a movement signal, is in fact not interpreted as a movement command perhaps because the population activity exhibits state space dynamics that are not optimal for evoking a movement 45-47 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also in line with the spike modulation times observed in burst generator neurons that participate in saccade generation 69,70 . It is generally stated the impact of reaching a threshold (equivalently, entering burst mode), either at individual or population activity, is to inhibit the brainstem omnipause neurons 67,71,72 , although other frameworks that depend on state space dynamical systems may facilitate direct communication between SC and pontine burst neurons 45-47 .…”
Section: Discussionmentioning
confidence: 99%